2016
DOI: 10.15171/mejdd.2016.33
|View full text |Cite
|
Sign up to set email alerts
|

Association between Pattern of Gastritis and Gastroesophageal Reflux Disease in Patients with Helicobacter Pylori Infection

Abstract: BACKGROUND Reflux disease is a common gastrointestinal problem. The association between reflux disease and gastritis pattern is controversial. AIM: To determine the association between reflux disease and gastritis pattern in patients with Helicobacter pylori (H. pylori) infection. METHODS 470 patients with dyspepsia and reflux disease were enrolled in this study. The inclusion criteria were willing to participate in the study, age over 40 years, and having the criteria of ROME III for at least 3 months. Patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 21 publications
2
5
1
1
Order By: Relevance
“…They found no relationship between hiatus hernia and H. pylori, which was inconsistent with our results. (21). In another study from Iran, they did not nd any association between H. pylori in patients with GERD compared to controls (22), which was consistent with our results.…”
Section: Discussionsupporting
confidence: 91%
“…They found no relationship between hiatus hernia and H. pylori, which was inconsistent with our results. (21). In another study from Iran, they did not nd any association between H. pylori in patients with GERD compared to controls (22), which was consistent with our results.…”
Section: Discussionsupporting
confidence: 91%
“…On the other hand, 42.6% of female students tested by serum antibody found to be seropositive for H. pylori infection with statistically significant 20 . Other studies showed overall 62% and 63.6% of women were infected with H. pylori 8,18 . Also, the seropositive prevalence of H. pylori infection were higher in women more than men 13 .…”
Section: Resultsmentioning
confidence: 91%
“…Таким образом, среди больных ГЭРБ c коморбидными кислотозависимыми заболеваниями преобладали лица с НЭРБ (с М-степенью и N-степенью изменений СО), что совпадает с результатами авторитетных исследований [14]. По результатам хромоскопии с конго красным для больных с ГЭРБ, коморбидной с ЯБДПК, были характерны состояния гипер-и нормохлоргидрии, а для больных ЯБЖгипо-и ахлоргидрии.…”
Section: Discussionunclassified